Long-Distance and Trans-Generational Stomatal Patterning by CO2 Across Arabidopsis Organs - Haus, Miranda J.; Li, Mao; Chitwood, Daniel H.; Jacobs, Thomas W. (Frontiers in Plant Science, 2018)
Stomata control water loss and carbon dioxide uptake by both altering pore aperture and developmental patterning. Stomatal patterning is regulated by environmental factors including atmospheric carbon dioxide (p[CO2]), which is increasing globally at an unprecedented rate. Mature leaves are known to convey developmental cues to immature leaves in response to p[CO2], but the developmental mechanisms are unknown. To characterize changes in stomatal patterning resulting from signals moving from mature to developing leaves, we constructed a dual-chamber growth system in which rosette and cauline leaves of Arabidopsis thaliana were subjected to differing p[CO2]. Young rosette tissue was found to adjust stomatal index (SI, the proportion of stomata to total cell number) in response to both the current environment and the environment experienced by mature rosette tissue, whereas cauline leaves appear to be insensitive to p[CO2] treatment. It is likely that cauline leaves and cotyledons deploy mechanisms for controlling stomatal development that share common but also deploy distinctive mechanisms to that operating in rosette leaves. The effect of p[CO2] on stomatal development is retained in cotyledons of the next generation, however this effect does not occur in pre-germination stomatal lineage cells but only after germination. Finally, these data suggest that p[CO2] affects regulation of stomatal development specifically through the development of satellite stomata (stomata induced by signals from a neighboring stomate) during spacing divisions and not the core pathway. To our knowledge, this is the first report identifying developmental steps responsible for altered stomatal patterning to p[CO2] and its trans-generational inheritance.